A Study of Steady Buoyancy-Driven Dissipative Micropolar Free Convection Heat and Mass Transfer in a Darcian Porous Regime with Chemical Reaction - Bég, O. Anwar Anwar; Bhargava, R.; Rawat, S.; Takhar, H. S. S.; Bég, Tasweer A. A. (Nonlinear Analysis: Modelling and Control, 2007)
In the present paper we examine the steady double-diffusive free convective heat and mass transfer of a chemically-reacting micropolar fluid flowing through a Darcian porous regime adjacent to a vertical stretching plane. Viscous dissipation effects are included in the energy equation. Assuming incompressible, micro-isotropic fluid behaviour the transport equations are formulated in a two-dimensional coordinate system (x, y) using boundary-layer theory. The influence of the bulk porous medium retardation is modeled as a drag force term in the translational momentum equation. Transformations render the conservation equations into dimensionless form in terms of a single independent variable, η, transverse to the stretching surface. A simplified first order homogenous reaction model is also used to simulate chemical reaction in the flow. Using the finite element method solutions are generated for the angular velocity field, translational velocity field, temperature and species transfer fields. The effects of buoyancy, porous drag and chemical reaction rate are studied. Chemical reaction is shown to decelerate the flow and also micro-rotation values, in particular near the wall. Mass transfer is also decreased with increasing chemical reaction rate. Increasing Darcy number is shown to accelerate the flow. Applications of the study include cooling of electronic circuits, packed-bed chemical reactors and also the near field flows in radioactive waste geo-repositories.